Evaluation of Two Parts of Lithocarpus polystachyus Rehd. from Different Chinese Areas by Multicomponent Content Determination and Pattern Recognition - Wei, Min (J Anal Methods Chem, 2020)
The purpose of this work is to establish a new method using high-performance liquid chromatography-diode array detection (HPLC-DAD) with chemometrics analysis to determine the content of catechin, isoquercetin, astragalin, phloridzin, trilobatin, and phloretin for one flavanol and five flavonoids, filter out the key compounds, and evaluate the quality of 26 batches of tender leaves and flower spikes of Lithocarpus polystachyus Rehd. (LP) from ten areas in China. The result showed that the HPLC-DAD method had excellent performance for accurate quantification analysis. S3 (tender leaf from Lushan, Sichuan) had the highest contents for six measured chemicals with trilobatin content of up to 27.82% in dry weight. S22 (flower spike from Liangping, Chongqing) had the highest content of phloridzin (up to 7.28%). All samples were divided into three types based on spatial distribution using principal component analysis. The result showed that the tender leaves and flower spikes from the same areas had many similar properties, and there were significant differences between the samples from different regions. Furthermore, phloridzin and trilobatin were identified as chemical markers for quality evaluation of two parts with different tender leaves and flower spikes of LP from geographical areas by orthogonal partial least squares discrimination analysis. These results will be helpful to establish an effective and comprehensive evaluation system of the development and utilization of LP resources.